SAFETY AND SECURITY ANALYSIS OF TOURISTS AT MARON BEACH SEMARANG: A QUALITATIVE STUDY ON WATER TOURISM MANAGEMENT - Nurdina Prasetyo; Pranoto, Pranoto (Ikatan Dosen Menulis, 2025)
This research explores the safety and security conditions of tourists at Maron Beach Semarang through a qualitative approach, employing participant observation, in-depth interviews, and document analysis. The study identifies several critical issues in safety and security management at this coastal tourism destination. Findings reveal significant challenges including inadequate safety equipment, shortage of professional rescue personnel, suboptimal supporting infrastructure, and ineffective coordination among relevant stakeholders. These discoveries offer important insights for developing safer and more sustainable water tourism management policies in the coastal region of Semarang.